ChemInform Abstract: The Fluoride Route to Lindqvist Clusters: Synthesis and Crystal Structure of Layered Hexatantalate Na8Ta6O19·26H2O. Issue 5 (13th February 2013) - Britvin, Sergey N.; Siidra, Oleg I.; Lotnyk, Andriy; Kienle, Lorenz; Krivovichev, Sergey V.; Depmeier, Wulf
Abstract The title compound is synthesized by reacting H2TaF7 with 7M aq.